FARS2 Mutations: More Than Two Phenotypes? A Case Report - Hotait, Mostafa; Nasreddine, Wassim; El-Khoury, Riyad; Dirani, Maya; Nawfal, Omar; Beydoun, Ahmad (Frontiers in Genetics, 2020)
FARS2, a nuclear gene, encodes the mitochondrial phenylalanyl-tRNA synthetase (mtPheRS). Previous reports have described two distinct phenotypes linked to FARS2 gene mutation: an early onset epileptic encephalopathy and spastic paraplegia. This report describes a distinctive phenotype of FARS2-linked, juvenile onset refractory epilepsy, caused by a hemizygous mutation in a compound heterozygous state (p.V197M and exon 2 microdeletion). A 17-year- old woman with normal development presented with a super refractory focal motor status epilepticus. Only an emergency life-saving surgery aborted her status after all therapeutic interventions, including anesthesia, failed to control her seizures. Pathological and biochemical activities on muscle biopsy showed mitochondrial proliferation with enhanced isolated activities of complexes II and IV, suggestive of a compensatory mechanism for the bioenergetic deficiency. Postoperatively, the patient started experiencing focal aware motor seizures originating from the contralateral hemisphere after being seizure free for a few months. This report suggests a third phenotypic manifestation of FARS2 gene mutation.